Penyuluhan Penyakit Kecacingan Ascariasis Kepada Masyarakat Desa Namorambe Kabupaten Deli Serdang - Christine Sibuea (LPPM Universitas HKBP Nommensen, 2022)
Ascariasis is a global problem helath with transmission through soil contaminated with helminth eggs. Personal and environmental hygiene as well as knowledge about ascariasis affect the risk of ascariasis. The purpose of this community service is to increase public knowledge about ascariasis. Outreach is given in poster media presentation, questions and answers with the community in Namorambe Village, Deli Serdang. Enthusiasm of the participants and the questions given showed the success of this activity. Education about personal and environmental hygiene and ascariasis needed to reduce the risk of ascariasis.